Vertical Bone Augmentation Using Two Bioactive Glasses in a Rabbit Tibia Model: A Comparative Study with Literature Review - Timur V. Melkumyan; Nuritdin Kh. Kamilov; Zurab S. Khabadze; Maria K. Makeeva; Gerhard K. Seeberger; Sargis S. Gevorgyan; Angela D. Dadamova (International Journal of Biomedicine, 2023)
Background: Recently, synthetic materials based on bioactive glasses have been in special demand in dental implantology, which, according to the mechanism of their action, are not only osteo-conductors, but also osteo-inductors. Of even greater interest is the fact that the biological degradation of these materials causes alkalization of the area and inhibits the growth of many pathogens. Considering the unique properties of this group of osteoplastic fillers and the problems associated with healing after guided bone regeneration, this study aimed to compare the effectiveness of using bioactive glasses S53P4 and 45S5 when performing vertical bone augmentation in an experiment applying a rabbit tibia model. Methods and Results: Six adult outbred rabbits aged from 1.5 to 2 years and weighing from 2.5 kg to 3.2 kg were used in the study. A titanium mesh was used to perform a true vertical guided bone regeneration technique. In each animal, two titanium tents were placed: one on the left tibia and one on the right tibia. On the left limb, empty spaces were filled with bioactive synthetic bone filler NovaBone® Morsels (USA); on the right limb, we used a mixture of bioactive glass Bonalive® granules CMF (Finland) and mineralized bone MedPark Bone-D XB (Bovine Xenograft, South Korea) in a ratio of 1:1. The quantity and quality of regenerated tissues were assessed after 8-10 weeks. The NovaBone application has allowed a gain of 2.6±2.67 mm in extra-skeletal hard tissue growth. No signs of guided bone regeneration were observed in all cases of application of an osteoplastic mixture of Bonalive and Bone-D XB granules. Conclusion: Within the limits of this study, it was found that the use of a mixture of bioactive glass Bonalive (S53P4) with bovine hydroxyapatite in a 1:1 ratio was not effective in vertically guided bone regeneration, but the application of NovaBone (45S5) could promote a new bone formation.